Work–life fit: identification of demand and resource typologies within a systems framework*. Issue 6 (2nd June 2016) - Turner, Michelle; Lingard, Helen
Abstract : Work–life fit occurs when people have the resources required to meet demands such that role performance (both at work and in non-work life domains) is effective. Interviews were conducted with 59 construction workers based in Melbourne, Australia to explore how demands and resources were experienced. Using a systems framework, data were analysed using thematic analysis. Results identified two demand typologies associated with demand-to-demand interaction. Demands operating as 'influencers' have a major impact on the conditions of the interdependent demand, while demands operating as 'creators' generate a new demand and shape the conditions of that demand. One resource typology related to resource–demand interaction was identified. 'Enabling resources' enable an individual to manage multiple demands across multiple domains, and may also enable an individual to manage multiple demands within a single domain. A new conceptual contribution is made to an area in which theory is under-developed, by adopting a systems approach to understanding the dynamic interactions between demands and resources. A lack of fit is damaging for the individual; therefore, it is useful to know that demands and resources are interdependent and these interdependencies will vary according to individuals. Using a systems approach to understanding demands and resources will be helpful to organizations seeking to support workers to achieve optimal work–life fit.